2018
DOI: 10.1021/acsphotonics.8b00982
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes for Quantum Dot Photovoltaics with Enhanced Light Management and Charge Transport

Abstract: Colloidal quantum dot (CQD)-based photovoltaics are an emerging low-cost solar cell technology with power conversion efficiencies exceeding 10%, i.e., high enough to be interesting for commercialization. Well-controlled and understood charge carrier transport through the device stack is required to make the next step in efficiency improvements. In this paper, polymer-wrapped single-walled carbon nanotube (SWNT) films embedded in an insulating poly­(methyl methacrylate) (PMMA) matrix and capped by a thermally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For example, Ihly et al demonstrated a remarkable performance enhancement of perovskite solar cell by introducing a SWNT interlayer between the perovskite layer and the HTL, which was attributed to the rapid hole extraction from the absorber layer with extremely slow back-transfer/recombination . In addition, Tazawa et al applied poly­(3-hexylthiophene-2,5-diyl)-wrapped SWNT to the CQDPV by embedding the composites into the poly­(methyl methacrylate) matrix, serving as a HTL, and observed significantly improved J SC owing to the fast carrier transfer . Both reports suggest that the SWNT incorporation into a solar cell can render lossless charge-transporting behavior within the device, resulting in improved charge carrier collection and, consequently, enhanced solar cell performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ihly et al demonstrated a remarkable performance enhancement of perovskite solar cell by introducing a SWNT interlayer between the perovskite layer and the HTL, which was attributed to the rapid hole extraction from the absorber layer with extremely slow back-transfer/recombination . In addition, Tazawa et al applied poly­(3-hexylthiophene-2,5-diyl)-wrapped SWNT to the CQDPV by embedding the composites into the poly­(methyl methacrylate) matrix, serving as a HTL, and observed significantly improved J SC owing to the fast carrier transfer . Both reports suggest that the SWNT incorporation into a solar cell can render lossless charge-transporting behavior within the device, resulting in improved charge carrier collection and, consequently, enhanced solar cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, Tazawa et al applied poly(3-hexylthiophene-2,5-diyl)-wrapped SWNT to the CQDPV by embedding the composites into the poly(methyl methacrylate) matrix, serving as a HTL, and observed significantly improved J SC owing to the fast carrier transfer. 37 Both reports suggest that the SWNT incorporation into a solar cell can render lossless charge-transporting behavior within the device, resulting in improved charge carrier collection and, consequently, enhanced solar cell performance. Also, another report suggested that improved stability in air could be achieved by introducing a semiconducting SWNT interlayer below the Au electrode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Green disposal at the end of the product lifecycle is also conceivable, as nanomaterial-based solar cells have the potential to be made entirely of carbon through rigorous separation, purification, and enrichment methods that guarantee the inherent properties of pure carbon at ideal levels [104]. Fourth-generation: nano photovoltaic Graphene-silicon 18.8% [87] 0-1 TBD TBD TBD Graphene-quantum dot 13.7% [88] Graphene-perovskite 16.1% [89] Graphene/perovskitequantum dot 17.9% [90] Graphene/quantum dot-perovskite 19.8% [91] Graphene-DSSC 11.5% [92] Carbon nanotubes-silicon 20.1% [93] Carbon nanotubes-quantum dot 6.00% [94] Carbon nanotubes-perovskite 37.4% [95] Carbon nanotubes-DSSC 10.3% [96] Graphene/carbon nanotubes-silicon 17.5% [97] Carbon nanotubes/graphenequantum dot 8.28% [98] Carbon nanotubes/silicon/graphenequantum dot 14.9% [99] Graphene/carbon nanotubes-perovskite 19.6% [100] Carbon nanotubes/graphene-DSSC 8.34% [101] These organic nanomaterials are also highly flexible as they can take on other forms of structure [105]. With their flexibility, scientists have created a variety of solar cells that silicon cannot produce.…”
Section: Solar Cell Technology In Generationsmentioning
confidence: 99%